Beyond borders: An analysis of free trade agreements and the competitiveness of the rice sector in Colombia - Andrade, R.; Ibarra, L. (2023)
Colombia lags in terms of competitiveness at the macro and meso levels. However, it appears to be a developing sector with opportunities for the future. At the micro level, the sector is already working to improve yields and reduce production costs through best practices. At the meso level, Colombia should focus on its quality standards to add value to its rice and penetrate other markets. Support to farmers is key to stabilize the crop without affecting market dynamics. In future work, we hope to complement the levels of analysis with more information and evaluate issues of technology adoption, production costs, subsidies and niche market dynamics.